The function given in the question is
![9x^2+y^2+18x-12y-180=0](https://img.qammunity.org/2023/formulas/mathematics/college/s79ro7avtp8cabkoykthlnb09jh29727pu.png)
Rearrange the function above connecting similar terms
![\begin{gathered} 9x^2+y^2+18x-12y-180=0 \\ 9x^2+18x+y^2-12y=180 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gmq3jhj9uh0lk3491wcepxyurqyv585bvh.png)
Factorize the equation in brackets
![\begin{gathered} 9x^2+18x+y^2-12y=180 \\ 9(x^2+2x)+1(y^2-12y)=180 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b7l1ekeg39c4jlce90capf38gj3vua4g0i.png)
Solve the brackets using completing the square method but multiplying the coefficient of x and y by 1/2 and then square
![\begin{gathered} 9(x^2+2x)+1(y^2-12y)=180 \\ 9(x^2+2x+(2*(1)/(2))^2)+1(y^2-12y+(-12*(1)/(2))^2=180+(2*(1)/(2))^2+(-12*(1)/(2))^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1ma1pi52po7ypn4d2e02a3yxnsc8yawpgs.png)
By simplifying the equation above, we will have
![\begin{gathered} 9(x^2+2x+(2*(1)/(2))^2)+1(y^2-12y+(-12*(1)/(2))^2=180+9(2*(1)/(2))^2+1(-12*(1)/(2))^2 \\ 9(x^2+2x+1)+1(y^2-12y+36)=180+9+36 \\ 9(x+1)^2+1(y-6)^2=225 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b7a1v2tpoga50ejtno22lp1iyfbj519lx3.png)
Divide all through by 225
![\begin{gathered} 9(x+1)^2+1(y-6)^2=225 \\ (9(x+1)^2)/(225)+(1(y-6)^2)/(225)=(225)/(225) \\ ((x+1)^2)/(25)+((y-6)^2)/(225)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/alq0bxg30uokgi7rj3ksnlp3adb8pgswj3.png)
The general formula for the equation of an ellipse is
![((x-h)^2)/(a^2)+((y-k)^2)/(b^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/l0626bn68eeug6hf6kdo2ks0r7t63wrkx6.png)
Where the center of the ellipse is
![(h,k)](https://img.qammunity.org/2023/formulas/mathematics/high-school/r1bijgiz1knkpv8mbwskalqzfunmt8qgad.png)
By comparing coefficients, we will have that
![\begin{gathered} x+1=x-h,y-6=y-k \\ x-x+h=-1,y-y+k=6 \\ h=-1,k=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1sa9k9dwj10em2knt9jx9jutryz1hu9me7.png)
The centre of the ellipse is
![\begin{gathered} (h,k)=(-1,6) \\ \text{hence,} \\ h+k=-1+6 \\ h+k=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/85u52lxzqh62jlzhd8en4ls3r0xhzglzxc.png)
Therefore,
The value of h+k = 5